Case of primary cutaneous peripheral T‐cell lymphoma, not otherwise specified, with characteristics of follicular helper T cells. Issue 6 (10th May 2014) - Takaki, Machiko; Inozume, Takashi; Matsuzawa, Takamitsu; Ando, Noriko; Yamaguchi, Miyuki; Harada, Kazutoshi; Kawamura, Tatsuyoshi; Shibagaki, Naotaka; Shimada, Shinji
Abstract We report a case of an 88‐year‐old woman with a decalvant, erythematous, ulcerated tumor extending from the right temporal to occipital region. Histopathological analysis revealed a dense infiltration of medium‐to‐large‐sized atypical cells throughout the entire dermis. The result of immunohistochemical analysis showed that the infiltrating T cells expressed programmed death‐1 (PD‐1), Bcl‐6 and CXCL13. Flow cytometry analysis showed that CD4+ PD‐1hi T cells also expressed CD10, inducible T‐cell co‐stimulator and CXCR5. On the basis of the clinical appearance and the histopathological findings, we diagnosed the patient with primary cutaneous peripheral T‐cell lymphoma, not otherwise specified. Recently, the concept of primary cutaneous follicular helper T (TFH)‐cell lymphoma was proposed, and in this case, tumor cells clearly expressed TFH‐cell markers. Therefore, we considered this case to be a variant of the entity. Although this entity is still provisional, this case supports the new concept.